Adequação nutricional e estado ponderal de adolescentes - Ribeiro, Paulina (2009)
Purpose: We aimed to assess nutritional adequacy, according to weight status in a sample of adolescents.Methods: We invited 544 adolescents (10 to 14 years) studying in a public school from Porto and 238 accepted to participate. A 24h recall questionnaire was used to assess food intake. Anthropometric measures (weight and height) were obtained, Body Mass Index (BMI) computed and overweight/obesity classified according to IOTS's cut-off points. Food Processor Plus 10.0 was used to convert food into nutrients. World Health Organization recommendations were used to estimate macronutrients adequacy and Dietary Reference Intakes from Food and Nutrition Board were used to evaluate micronutrient adequacy. T-test and Mann-Whitney test were used to compare nutritional intake between normal and overweight/obese adolescents. Proportions were compared by Chi-square test.Results: Compared to overweight/obese, normal weight girls reported higher mean intake of energy, protein, saturated fat, thiamin, riboflavin, copper, magnesium, phosphorus, zinc and calcium and lower intake of vitamin B12. Normal weight boys reported higher mean intake of carbohydrate, fiber, vitamin A, thiamin, riboflavin, vit.B6, folate and iron. Compared to overweight/obese, normal weight adolescents showed higher adequacy prevalence for the following nutrients: in girls, thiamin, magnesium, zinc and phosphorus; in boys, riboflavin, folate, iodine, magnesium and selenium. Independently of weight status, adolescents reported excessive intakes of protein, total fat and sugars, and low intake of fiber.Conclusion: In general, overweight/obese adolescents reported higher nutritional inadequacy prevalence than normal weight ones.